A Reference Model to Assess the Underground Environment in National IED Plants - Francesca Mauro; Alessandro Stracqualursi; Marzio Zanellato; Francesco Zampetti; Roberto Borghesi (Chemical Engineering Transactions)
Industrial pollution has been accounted to produce several impacts on the environment, thus stimulating a complex environmental governance all over the world. At a European level, the directive 2010/75/EU (so called IED Directive) promoted the adoption of the Best Available Techniques (BAT) to address and reduce environmental impacts related to industrial plants. The focus of this paper is to show the model elaborated by Italian Institute for Environmental Protection and Research (ISPRA) to assess some “baseline reports”, with reference to soil and groundwaters monitoring. More in detail, the study starts from the analysis of technical documents sent by Italian operators to the national competent authority (MASE) for the implementation of the IED Directive. The proposed model was developed starting from the data investigation related to 15 installations, in compliance with national and European guidelines on the theme. Further research perspectives could rise from using such a model to identify critical and open points in the field.